Aortic valve replacement with essential thrombocythemia. (February 2019) - Yuzaki, Mitsuru; Honda, Kentaro; Kaneko, Masahiro; Nakai, Takeo; Kunimoto, Hideki; Nishimura, Yoshiharu
Cardiac surgery in patients with essential thrombocythemia carries the risks of both thrombotic events and a bleeding tendency. We report the case of a 75-year-old man with essential thrombocythemia who underwent successful surgical aortic valve replacement after his platelet count was controlled with plateletpheresis 3 times before surgery.